Reduction of Side Effects by Segmented Electrodes in Case of Subthalamic Nucleus Deep Brain Stimulation in Parkinson Disease: A Case Report. - Frank, P. Schwarm; Iris, Reuter; Maximilian, Swoboda; Eberhard, Uhl; Malgorzata, A. Kolodziej (Journal of Neurological Research And Therapy, 2019)
Patients suffering treatment resistant Parkinson´s disease (PD) are potential candidates for deep brain stimulation (DBS). Commonly most implanted electrodes have a cylindrical shape with quadripolar electrode contacts and generate a symmetrical stimulation field around the lead. To reduce side effects through activation of neighboring fibers a new electrode design with segmented contacts was developed and enables a better adaption of the field of stimulation as well as a multi-target stimulation to improve therapeutic benefits. We report about a 51-year-old male patient with a 15-year history of treatment-refractory PD, who was implanted with bilateral segmented electrodes in the subthalamic nucleus (STN) with St. Jude Medical Infinity™ DBS System (Abbott/St. Jude Medical, Saint Paul, Minnesota, USA). Despite a clear mood-enhancing effect, stimulation with ring electrodes caused motor side effects including rigor and speech disorder. With segmented electrodes an effective and gentle stimulation was achieved. The stimulation of the anterior segments in the central position of the electrode in the STN showed no side-effects and allowed a reduction of initial symptoms in an low stimulation amplitude. Despite precise preoperatively planning and intraoperative trial stimulation, side effects of STN stimulation are very common. The application of segmented electrodes permits more options to reduce side effects rather than using ring electrodes. Studies with larger sample sizes are needed to establish the optional DBS electrode.
Keywords: Deep brain stimulation; Parkinson disease; segmented electrodes